Disparitas Desentralisasi; Konsepsi Otonomi Daerah Khusus Ibukota terhadap Sistem Ketatanegaraan Indonesia - Hakam Bath, Akbar Shah (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2024)
Regional autonomy and autonomous regions in Indonesia are affirmed in Article 18 of the 1945 Constitution, providing the constitutional basis for the regional governance system. Ideally, regional autonomy enables regions to independently and effectively manage their governmental affairs. However, in reality, there is a discrepancy (disparity) between theory and practice, particularly in the context of the Special Autonomous Region of the Capital City. This study is a literature-based research with a qualitative approach, employing normative juridical methodology. The study concludes that the establishment of the Special Autonomous Region of the Capital City should first comply with the provisions of Article 18 of the 1945 Constitution, and only then consider Article 18B, especially in the context of relocating the capital city to East Kalimantan. Article 18 of the 1945 Constitution emphasizes the "principle of autonomy" in regional governance, particularly for special regions like the Special Autonomous Region of the Capital City. The formation of the Special Autonomous Region of the Capital City must align with the requirements of Article 18 of the 1945 Constitution before considering Article 18B, particularly in the context of the capital relocation plan.